2021
DOI: 10.4314/jcsia.v28i1.9
|View full text |Cite
|
Sign up to set email alerts
|

A FrontPage Online News Analysis: An Opinion Mining Approach

Abstract: The advent of the internet with its attendant democratization of data and deluge of information had given rise to the avalanche of news media agencies. These agencies publish news articles with varying emotional reports especially stories conveying bad sentiments to the public. As major news agencies operate micro-blogging websites and establish their presence on social media channels, the distribution of bad news increases. It has been shown that constant exposure to bad news presented in a body of texts, gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…AI techniques used for emotion detection Ogbuju et al (2021) presented research that detects emotions from online news/text. The authors used twelve (12) different online news channels in Nigeria as datasets to train the proposed model and a hybrid method of corpus-based lexicon and dictionary approaches to achieve the research aim.…”
Section: Answers To Rq3mentioning
confidence: 99%
“…AI techniques used for emotion detection Ogbuju et al (2021) presented research that detects emotions from online news/text. The authors used twelve (12) different online news channels in Nigeria as datasets to train the proposed model and a hybrid method of corpus-based lexicon and dictionary approaches to achieve the research aim.…”
Section: Answers To Rq3mentioning
confidence: 99%
“…To show the prevalence of the health issues caused by the reading text messages, Shalaby et al (2022) demonstrated Text2quit and Quit4baby, two texting service programs to help people cease from smoking addiction; and Text4Mood and Text4Support, two other mobile text messaging programs to help people with mood disorders and other mental health conditions, including alcohol use disorder. Health issues such as heart attack, high blood pressure, hypertension, stroke and even bowel disorder can occur due to negative messages as noted by Ogbuju et al (2021) which also demonstrated that having a system that filters and block negative emotions in text messages from getting to the user will be of great help in reducing the impact of these health matters on our communities.…”
Section: Introductionmentioning
confidence: 99%